Involvement of Alternative Splicing in Barley Seed Germination - Zhang, Qisen; Zhang, Xiaoqi; Wang, Songbo; Tan, Cong; Zhou, Gaofeng; Li, Chengdao (PLOS ONE, 2016)
Seed germination activates many new biological processes including DNA, membrane and mitochondrial repairs and requires active protein synthesis and sufficient energy supply. Alternative splicing (AS) regulates many cellular processes including cell differentiation and environmental adaptations. However, limited information is available on the regulation of seed germination at post-transcriptional levels. We have conducted RNA-sequencing experiments to dissect AS events in barley seed germination. We identified between 552 and 669 common AS transcripts in germinating barley embryos from four barley varieties (Hordeum vulgare L. Bass, Baudin, Harrington and Stirling). Alternative 3’ splicing (34%-45%), intron retention (32%-34%) and alternative 5’ splicing (16%-21%) were three major AS events in germinating embryos. The AS transcripts were predominantly mapped onto ribosome, RNA transport machineries, spliceosome, plant hormone signal transduction, glycolysis, sugar and carbon metabolism pathways. Transcripts of these genes were also very abundant in the early stage of seed germination. Correlation analysis of gene expression showed that AS hormone responsive transcripts could also be co-expressed with genes responsible for protein biosynthesis and sugar metabolisms. Our RNA-sequencing data revealed that AS could play important roles in barley seed germination.